Das urologische Studienregister der DGU - Kunath, Frank; Becker, C.; Jena, S.; Antes, G.; Wullich, Bernd (Urologe, 2011)
Germany is an important hub for urological research and clinical trials are therefore very important for evidence-based medicine. In September 2010, the German Society of Urology commissioned a subject-specific clinical trial registry. The broad overview of ongoing and completed clinical trials in urology should help to increase transparency in research and to deploy resources in health care more efficiently. The urological trial registry aims to negotiate cooperation with a national primary registry to allow an automatic inclusion in the WHO Registry Network and to enable an ICMJE-compliant registry. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2025-08-19
Keywords: Evidence-based medicine; Germany; Publication bias; Registries; Urology